(untitled) (South Asian Journal of Agriculture, 2025)
Nitrogen Use Efficiency (NUE) integrates nitrogen (N) in different crop parts and depends upon the sources from which it derives. Higher NUE is essential for high yield potential and minimizing N loss after addition in soil. For this, a pot experiment was set up to evaluate the NUE of three boro rice varieties which are BRRI dhan61, BRRI dhan68, and BRRI dhan28 considering two sources of commercial urea fertilizer. These sources were termed as T1 (Urea, Kingdom of Saudi Arabia origin) and T2 (Urea, Qatar origin) while the control treatment was designated as T0. All the pots were arranged in a completely randomized design with four replications. Various NUE parameters such as partial factor productivity (PFP), crop recovery efficiency (CRE), agronomic efficiency (AE) and physiological efficiency (PE), agronomic as well as yield contributing characteristics of rice were studied. Results indicated that T1 showed the highest PFP, CRE, and AE in BRRI dhan68 which were 34.43 kg kg-1, 0.70 kg kg-1, and 26.32 kg kg-1, respectively, whereas the highest PE (81.58 kg kg-1) was observed in BRRI dhan28 with T2. All the rice varieties showed the highest nitrogen uptake by grain when treated with T1. Maximum grain yield (30.99 g pot-1) was found in BRRI dhan68 in T1 treated soil, which increased by 13.65% and 33.11% from BRRI dhan61 and BRRI dhan28, respectively. Agronomic as well as yield contributing characteristics such as height, tiller per plant, panicle per plant, straw yield, etc. were also highest in T1-treated soil irrespective of the rice plant studied. Considering the results of this experiment, it can be concluded that T1 treatment has a relative advantage compared to T2 used as nitrogen fertilizer sources because it enhanced N use efficiencies and may lead to reduced N losses in rice production. South Asian J. Agric., Vol. 10, No.1-2, 2024: 62-71